Designing a Tourist Attractions Information System Using the Design Thinking Method (Case Study: Maimoon Palace) - Hasibuan, M. Haviz; Hasdiana, Hasdiana; Lubis, Fachrul Rozi (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2020)
Maimoon Palace is one of the tourist attractions and cultural heritages that has high potential, both in Medan and Indonesia. However, in the digital era, Maimoon Palace does not have an Information System which can give information about its availability, while it does not provide online ticketing as well. This underlies the writer to create Web Based Tourism Information System of Maimoon Palace. This research uses direct observation method, interview with related parties, and literature studies related to the issues. Web Based Tourism Information System of Maimoon Palace is generated by PHP and HTML programming language and MySQL database. This system uses design thinking system development method. Design Thinking is the method utilized by the writer to solve the problem with user-centered approach to define the problem, thenceforth to conceptualize ideas as a solution to produce a system. This information systems can be used to give the information about Maimoon Palace availability to the visitors and can be used to book the ticket online. This system is expected to be useful as information and media promotion for tourism potential in Medan. The more tourists visit Maimoon Palace, the more income will be gained by the people surround Maimoon Palace. Keyword: Information System, Tourist Attractions, Design Thinking, Maimoon Palace